Aggressive Recurrence of Primary Hepatic Epithelioid Haemangioendothelioma after Liver Transplantation - Qusay A. Abdoh; Asma M. Alnajjar; Faisal A. Abaalkhail; Mohammed Al Sebayel; Hussa F. Al-Hussaini; Waleed K. Al-Hamoudi; Hazem Helmy; Mohamad Almansour; Hussien A. Elsiesy (Canadian Journal of Gastroenterology and Hepatology)
HEHE is a rare neoplasm of vascular origin that occurs in the liver; UNOS reported a favorable outcome after liver transplantation in 110 patients with 1-year and 5-year survival of 80% and 64%. Case Report. A 40-year-old lady presented with a three-month history of right upper abdominal pain with nausea, vomiting, and significant loss of weight associated with scleral icterus and progressive abdominal distension. Examination revealed jaundice, hepatomegaly, and ascites. Serum bilirubin was 26.5 mg/dL and ALP was 552 CT. Abdomen and pelvis showed diffuse infiltrative neoplastic process of the liver with a mass effect and stretching of the hepatic and portal veins, in addition to bile duct dilatation. Viral hepatitis markers were negative and serum alpha fetoprotein was within reference range. Liver biopsy was consistent with HEHE, with positive endothelial markers (CD31, CD34, and factor VIII-related antigen). She underwent living related liver transplantation on June 2013 and was discharged after 20 days with normal liver enzymes. Four months later, she presented with diffuse disease recurrence. Liver biopsy confirmed disease recurrence; she received supportive treatment and unfortunately she died 2 weeks later. Conclusion. HEHE can have rapid and aggressive recurrence after liver transplantation.